Commercialization of Rice and Vegetables Value Chains in Lao PDR : Status and Prospects - World Bank Group (World Bank, Washington, DC, 2018)
Rice is Lao PDR’s biggest agricultural commodity in terms of farmers involved in production, cropland area allocated, and food consumption. Rice also generates important economic spillover effects, supporting jobs in milling, trading, and food catering sectors nationwide. Vegetables are emerging as a new source of growth, benefiting from the rising demand of more affluent and urbanized Laotians for nutritious and diverse diets. This report studies the extent of commercialization of rice and vegetables value chains in Lao PDR, the main challenges and opportunities, and ways to increase their contribution to the country’s economic development. Economic benefits are maximized when farmers have incentives to produce for profit while consumers gain from reasonable prices and good quality of products. Therefore, this report focuses on the cost buildup between farmers and consumers, motivated by the high retail rice prices in Vientiane vis-à-vis complaints of low farm-gate prices. The report follows a qualitative and quantitative value chain approach combined with a detailed regulatory assessment. It is based on about 100 interviews with key experts and stakeholders. It studies the value chain for rice from Khammouane to Vientiane Capital and for vegetables from Vientiane Province to Vientiane Capital. Theresults are not country representative; they should be read as a snapshot of the selected value chains in selected areas in 2017. Yet this work is unique for Lao PDR, among the first to generate detailed estimates of cost build-up at each stage of the value chain using primary data and applying a consistent methodology. It is also unique in generating knowledge on the vegetables value chain, which is less studied than those of rice and other agricultural commodities in Lao PDR. The study finds that Lao farmers receive a relatively high farm-gate price, yet high production costs “eat” their profits (rather than low farm-gate prices, as often perceived in the country). However, the share of farm-gate prices in wholesale and retail prices in Lao PDR is the lowest among its peers. This dampens farm supply responses. In addition, the issues holding back the rice sector in Lao PDR pertain to: (i) low productivity and quality management at the farm and immediate post farm levels; (ii) a fragmented milling sector dominated by small operators with old technology; (iii) an overall market system that fails to provide incentives for product quality; and (iv) the lack of a significant consumer class with high purchasing power that could foster consolidation of wholesale and retail sectors and reduce their costs. In summary, the high cost of paddy production and operational inefficiencies among multiple players in the value chain areresponsible for high consumer rice prices.